2019
DOI: 10.1002/lary.27664
|View full text |Cite
|
Sign up to set email alerts
|

Incidental thyroid papillary microcarcinoma: survival and follow‐up

Abstract: Objectives/Hypothesis: The aim was to study the survival of incidental thyroid papillary microcarcinoma patients treated with surgery for benign thyroid disease to validate absence of oncological follow-up and reduce unnecessary health expenses.Study Design: Retrospective cohort study. Methods: We analyzed patient's files and interviewed 252 patients by telephone whose cases were submitted to the multidisciplinary meeting of thyroid pathology in Strasbourg, France, for incidental thyroid papillary microcarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Cervical LNM is a common finding in PTC, affecting 20% to 80% of patients [20,21]. Some authors state that clinically evident cervical LNM seems to be the fundamental indicator in terms of prognosis [32]. PTC frequently recurs in regional lymph nodes [28] and cervical LNM, at initial surgery, increases the incidence of recurrent disease during follow-up [30,32] and decreases DSS in some studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical LNM is a common finding in PTC, affecting 20% to 80% of patients [20,21]. Some authors state that clinically evident cervical LNM seems to be the fundamental indicator in terms of prognosis [32]. PTC frequently recurs in regional lymph nodes [28] and cervical LNM, at initial surgery, increases the incidence of recurrent disease during follow-up [30,32] and decreases DSS in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors state that clinically evident cervical LNM seems to be the fundamental indicator in terms of prognosis [32]. PTC frequently recurs in regional lymph nodes [28] and cervical LNM, at initial surgery, increases the incidence of recurrent disease during follow-up [30,32] and decreases DSS in some studies. Controversy exists regarding appropriate surgical management of cervical lymph nodes without evidence of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Although PTMC is characterized as a kind of indolent tumor, the presence of lymph node metastasis always relates to unfavorable oncological outcomes. According to previous studies, about 25% to 64% of patients with PTMC have cervical lymph node metastasis (CLNM) ( 3 ), especially in the central compartment ( 4 , 5 ). Meanwhile, PTMC patients with CLNM exhibit a high recurrence rate compared to those without CLNM ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid microcarcinoma (TMC) refers to thyroid cancer with diameter ≤ 1 cm, also known as occult thyroid cancer [1,2]. TMC has a high prevalence in the population and a previous autopsy study on subjects who died of non-thyroidal diseases revealed latent TMC in up to 5.2% of the subjects [1,3].…”
Section: Introductionmentioning
confidence: 99%